Diabetes disturbs functional adaptation of the remote myocardium after ischemia/reperfusion. (December 2022) - Funk, Florian; Kronenbitter, Annette; Isić, Malgorzata; Flocke, Vera; Gorreßen, Simone; Semmler, Dominik; Brinkmann, Maximilian; Beck, Katharina; Steinhoff, Oliver; Srivastava, Tanu; Barbosa, David Monteiro; Voigt, Katharina; et al.
Abstract: Diabetes mellitus type 2 is associated with adverse clinical outcome after myocardial infarction. To better understand the underlying causes we here investigated sarcomere protein function and its calcium-dependent regulation in the non-ischemic remote myocardium (RM) of diabetic mice (db/db) after transient occlusion of the left anterior descending coronary artery. Before and 24 h after surgery db/db and non-diabetic db/+ underwent magnetic resonance imaging followed by histological and biochemical analyses of heart tissue. Intracellular calcium transients and sarcomere function were measured in isolated cardiomyocytes. Active and passive force generation was assessed in skinned fibers and papillary muscle preparations. Before ischemia and reperfusion (I/R), beat-to-beat calcium cycling was depressed in diabetic cardiomyocytes. Nevertheless, contractile function was preserved owing to increased myofilament calcium sensitivity and higher responsiveness of myocardial force production to β-adrenergic stimulation in db/db compared to db/+. In addition, protein kinase C activity was elevated in db/db hearts leading to strong phosphorylation of the titin PEVK region and increased titin-based tension of myofilaments. I/R impaired the function of whole hearts and RM sarcomeres in db/db to a larger extent than in non-diabetic db/+, and we identified several reasons. First, the amplitude and the kinetics of cardiomyocyte calcium transients were further reduced in the RM of db/db. Underlying causes involved altered expression of calcium regulatory proteins. Diabetes and I/R additively reduced phospholamban S16-phosphorylation by 80% ( P < 000.1) leading to strong inhibition of the calcium ATPase SERCA2a. Second, titin stiffening was only observed in the RM of db/+, but not in the RM of db/db. Finally, db/db myofilament calcium sensitivity and force generation upon β-adrenergic stimulation were no longer enhanced over db/+ in the RM. The findings demonstrate that impaired cardiomyocyte calcium cycling of db/db hearts is compensated by increased myofilament calcium sensitivity and increased titin-based stiffness prior to I/R. In contrast, sarcomere function of the RM 24 h after I/R is poor because both these compensatory mechanisms fail and myocyte calcium handling is further depressed. Graphical abstract: Unlabelled Image Highlights: The remote myocardium is key to maintain cardiac function after MI. SERCA2a activity is largely reduced in diabetic db/db remote myocardium. Increased Ca2+ sensitivity and titin stiffness stabilize myofilament function. These compensatory mechanisms fail in db/db remote myocardium.